PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KEBERAGAMAAN DALAM PEMBELAJARAN PAI DI SMAN 30 JAKARTA - Ismi Farah Azizah; Muhamad Ariz Hibrizi; Aulawia Hidayati; Rio Permata Hati (CV. ADIBA AISHA AMIRA, 2025)
This research aims to develop interactive learning media that is effective in increasing students' understanding of religious diversity in Islamic Religious Education (PAI) subjects at the high school level. Using research and development (R&D) methods with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model, this research produced a word search-based educational game called